Development of Aedes aegypti L. under the action of light radiation at different wavelengths - Walquíria Vieira Monteiro Paiva; Sérgio de Sá Leitão Paiva Júnior; Edvaldo da Nóbrega Gaião; Plínio Pereira Gomes Júnior (Acta Scientiarum: Biological Sciences, 2023)
Aedes aegypti is a holometabolous insect, vector of medical importance for arboviral transmission, and has shown the ability to develop chemical larvicides resistance, which are the worldwide used to control mosquitoes’ population because of their low cost. Due to the well-known photophobia, a striking characteristic of the behavior of A. aegypti larvae, this study aimed to observe the development of this insect in its larval stage under the action of certain ranges of light radiation and its possible biological effects. For that, the experiments used larvae in L1, observed during seven days under the action of LEDs (light-emitting diode) that emitted light at different wavelengths, with six different colors, one for each experiment. Some were tested with a light-dark interval every 10 minutes and others every two minutes, with three repetitions. At the end, mosquitoes, pupae and larvae were counted and the data submitted to statistical evaluation. The experiment showed a significant difference between the control and the different wavelengths used, when exposed at two-minute intervals. LEDs that emitted blue (λ = 457.9 nm) and white (λ = 448.58 nm) wave frequencies were the most promising for the development of equipment that could act synergistically with other forms of control in order to improve its efficiency.